Community Norms and Human Rights: Supervising Haitian Colleagues on Interpersonal Psychotherapy (IPT) With a Depressed and Abused Pregnant Woman. Issue 8 (17th August 2016) - Verdeli, Helen; Therosme, Tatiana; Eustache, Eddy; Hilaire, Olissaint St; Joseph, Benissois; Sönmez, Cemile Ceren; Raviola, Giuseppe
Abstract : After the 2010 Haiti earthquake, Zanmi Lasante, a local health care organization, implemented a collaborative stepped‐care model to address depression in community and primary care settings in rural Haiti. Specialized community health workers, the ajans santé, collaborate with local psychologists and primary care doctors to offer home‐based evaluation, support, and follow‐up. The services include brief interpersonal psychotherapy (IPT) and/or medication to persons who met locally defined criteria for depression. A cross‐national (Haiti–United States) expert mental health team has been overseeing the program. The present IPT supervision case of a severely depressed, physically abused, and pregnant young woman illustrates the U.S.‐based supervisor's internal struggle to reconcile awareness of and respect for local norms while maintaining a human rights‐based framework. It also highlights the critical role of community health workers in addressing the mental health treatment gap in regions plagued by extreme poverty and adversity.